Investigation of approaches to modeling of intercity passenger transportation system - Dolya, Constantine; Botsman, Anastasiia; Kozhyna, Viktoriia (Technology audit and production reserves, 2017)
The modern scientific approaches to the issue of establishing passenger correspondence using public routes between regional centers are investigated. The results of the analysis of the existing methods for calculating the correspondence of passengers find the impossibility of their implementation without a preliminary study of the features of the system and formalization of corrective coefficients - the components of the gravity functions. It is established that at present in the world practice gravitational modeling is used for forecasting the indicators of interregional passenger transport correspondence. An empirical method is used to establish the parameters of the quantitative index of the gravity function. Unlike previous researchers, used for the invention of the parameters of the function of the attraction approach allows to obtain new knowledge about the studied system. Without the use of automated or non-automated means for examining the correspondence of passengers, it is possible to obtain indicators of the parameters of the experimental system without the influence of the human factor and any time interval. The obtained research results provide an opportunity to carry out calculations of the correspondence of passengers between the regional centers of Ukraine on the routes of general transport using the gravity model. Unknown parameters of gravity function are established in the conducted research. They provide an opportunity in forecasting the correspondence of passengers in the investigated system.